ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI BELANJA MODAL PADA PROVINSI JAWA TIMUR - Febriana, Imas Sherli; Praptoyo, Sugeng (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to result of the influence of Local Own Sources Revenue (PAD),General Allocation Fund (DAU), Special Allocation Fund (DAK) and Budget Financing Surplus(SILPA) to the Capital Expenditure (BM). The independent variables are Local Own Source Revenue(PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK) and Budget FinancingSurplus (SILPA). Meanwhile, the dependent variable is using Capital Expenditure (BM). The samplesare 29 districts and 9 cities in East Java Province and the research is a three-year periods in 2012-2014fiscal years. The sample collection technique has been done by using purposive sampling. Thegovernment data is in the form of secondary data in the APBD Realization statement of East JavaGovernance in 2010-2014. The analysis method has been done by using multiple linear regressions.The result of this research shows that (1) Local Own Source Revenue (PAD) has influence to theCapital Expenditure (BM), (2) General Allocation Fund (DAU) has influence to the capital expenditure(BM), (3) Special Allocation Fund (DAK) does not have any influence to the capital expenditure, (4)Budget Financing Surplus (SILPA) does not have any influence to the capital expenditure.Keywords: Local Own Sources Revenue, General Allocation Fund, Special Allocation Fund, Budget FinancingSurplus, Capital Expenditure.